Integrating scholarly content: Semantic approach - Ismail M.A.; Yaacob M.; Kareem S.A. (2023)
Semantic Web provides a new paradigm in the web technology that aims to support the description of the heterogeneous resources on the web into a machine readable manner. The main advantage of Semantic Web, in terms of integration is that it provides a different approach of integrating new databases with existing databases which is done at the semantic layer. In solving the issue of interoperability between these publishing mediums, the utilization of scholarly metadata are taken into consideration. This paper highlights the issues surrounding the integration of scholarly content such as thesis and journal databases. The semantic approach as a solution for these problems is described in detail pertaining to the data gathered from Electronic Journal of University of Malaya (EJUM), Electronic Conference and Electronic Thesis databases.